Re-hospitalization and its impact factors among depression patients in Chengdu city, 2013 − 2017 - Shi-yi LIAO; Yang-yang WANG; Yan CAI (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo study the status and influencing factors of readmission in depression patients. MethodsFrom Chengdu Municipal Medical Insurance Administration, Sichuan province, we collected 25 043 medical and reimbursement records for 16 556 depression patients having hospitalizations during the period from 2013 through 2017; the hospitalization status of the patients was analyzed. Rank-sum test and Chi-square test were used in analysis on hospitalization-related difference among subgroups of the patients; logistic regression model was used to analyze influencing factors of some patients' readmission. ResultsThe person-times of depression patient's hospitalization for 10 000 population increased from 1.92 in 2013 to 5.35 in 2017 and the person-times was higher for female population than for male population. Among all depression patients studied, the number of readmission within 30 days of discharge was 1 519 and 30-day readmission rate was 9.17%; the total number of readmission during the 5-year period was 3 854 and the 5-year readmission rate was 23.28%. The readmission rate was lower in the patients with medical insurance for urban and rural residents than that in the patients with medical insurance for urban workers. For all the re-hospitalizations recorded, the top three diagnosis at the readmission were mental and behavioural disorders (coded with F00-F99 in International Classification of Diseases and Related Health Problems, Tenth Revision [ICD-10], accounting for 28.35% of total re-hospitalization), circulatory diseases (I00-I99, 20.17%), and respiratory diseases (J00-J99, 16.27%), respectively. Logistic regression analysis showed that female gender, aged ≥20 years, covered by medical insurance for urban workers, having the hospital stay of ≥ 8 days, and being diagnosed as recurrent depression (ICD-10 code: F33) were significant risk factors for re-hospitalization of depression patients; while, having comorbidity disease and being hospitalized in primary/secondary/tertiary hospital were significant protective factors against readmission. ConclusionThe ratio of readmission was high among depression patients ever being hospitalized in Chengdu city and the re-hospitalization is mainly influenced by gender, age, medical insurance type, length of stay, depression type, comorbidity, and the grade of hospital providing hospitalization.